2021
DOI: 10.1177/09670335211025649
|View full text |Cite
|
Sign up to set email alerts
|

The use of near infrared spectroscopy to predict foliar nutrient levels of hydroponically grown teak seedlings

Abstract: Due to a combination of durability, strength, and aesthetically pleasing color, teak ( Tectona grandis L.f.) is globally regarded as a premier timber species. High value, in combination with comprehensive harvesting restrictions from natural populations, has resulted in extensive teak plantation establishment throughout the tropics and subtropics. Plantations directly depend on the production of healthy seedlings. In order to assist growers in efficiently diagnosing teak seedling nutrient issues, a hydroponic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…In the current study, it was found that the NIRS system had a very good potential to predict the K content of the dried and ground pistachio tree leaves ( R 2 > 0.80) from the NIR reflectance data. The performance of the model developed for the K content determination was observed to have similar success ( R 2 > 0.80) compared to other studies conducted using NIRS on different plant leaves (Gálvez‐Sola et al., 2015; Whittier et al., 2021; Yarce & Rojas, 2012). Predictions of Ca, Cu, Mg, and Fe concentrations also exhibit modest yet reasonable performance ( R 2 = 0.70–0.80), which is comparable to or even superior to certain NIRS‐utilizing studies (Cuq et al., 2020; Gálvez‐Sola et al., 2015; Sekerli et al., 2021a, 2021b; Whittier et al., 2021; Yarce & Rojas, 2012).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the current study, it was found that the NIRS system had a very good potential to predict the K content of the dried and ground pistachio tree leaves ( R 2 > 0.80) from the NIR reflectance data. The performance of the model developed for the K content determination was observed to have similar success ( R 2 > 0.80) compared to other studies conducted using NIRS on different plant leaves (Gálvez‐Sola et al., 2015; Whittier et al., 2021; Yarce & Rojas, 2012). Predictions of Ca, Cu, Mg, and Fe concentrations also exhibit modest yet reasonable performance ( R 2 = 0.70–0.80), which is comparable to or even superior to certain NIRS‐utilizing studies (Cuq et al., 2020; Gálvez‐Sola et al., 2015; Sekerli et al., 2021a, 2021b; Whittier et al., 2021; Yarce & Rojas, 2012).…”
Section: Discussionsupporting
confidence: 62%
“…The performance of the model developed for the K content determination was observed to have similar success ( R 2 > 0.80) compared to other studies conducted using NIRS on different plant leaves (Gálvez‐Sola et al., 2015; Whittier et al., 2021; Yarce & Rojas, 2012). Predictions of Ca, Cu, Mg, and Fe concentrations also exhibit modest yet reasonable performance ( R 2 = 0.70–0.80), which is comparable to or even superior to certain NIRS‐utilizing studies (Cuq et al., 2020; Gálvez‐Sola et al., 2015; Sekerli et al., 2021a, 2021b; Whittier et al., 2021; Yarce & Rojas, 2012). However, this technique did not offer good results for the prediction of N, P, Zn, and Mn in the present study ( R 2 < 0.70).…”
Section: Discussionsupporting
confidence: 62%
“…Photos of S-deficient seedlings in greenhouses have been published (Goslin 1959;Murison 1960;Hacskaylo et al 1969;Erdmann 1979;Whittier 2018) but they have not been published when grown outside in bareroot nurseries (Benzian 1965a;Bengtson 1968;Truman 1972;Baer 1984;. This is likely due to use of sulphate fertilizers plus irrigation water containing S plus atmospheric deposition.…”
Section: Deficiency Symptomsmentioning
confidence: 99%
“…However, most of the nutrient minerals of fruit trees are present in organic matter and combined with one of the abovementioned moieties, so quantitative and qualitative analyses of nutrients can be achieved indirectly by NIR spectroscopy. 10 For example, Whittier et al 11 used NIR spectroscopy to predict the foliar nutrient levels of hydroponically grown teak seedlings. Bedin et al 12 detected C, N, P, and K in poultry litter by NIR spectroscopy via support vector machine (SVM) and achieved good results.…”
Section: Introductionmentioning
confidence: 99%